The panda puzzle - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2002)
Dink, Josh, and Ruth Rose investigate the kidnapping of the new baby panda at the petting zoo.
"A Stepping Stone book."
"P"--Spine.
3.5
3-6
3-6
450
Keywords: Giant panda -- Fiction; Pandas -- Fiction; Zoos -- Fiction; Mystery and detective stories; Giant pandas -- Fiction; Pandas -- Fiction; Zoos -- Fiction; Mystery fiction